Factors influencing hydrothermal pretreatment of banana peel for high recovery of pectin oligosaccharides (POS) - Nur Irdina Izzati, Zakaria; Mohd Shafiq, Mohd Sueb; Shariza, Jamek (Universiti Malaysia Pahang, 2024)
Utilizing banana peels creates opportunities for technological advancement in the direction of production strategies for food ingredients. Banana peel is an inexpensive by-product that can be processed into oligosaccharides with significant added value that has been reported to benefit food, animal feed and human health. Recently, pectin oligosaccharides (POS) have been the main research subject on banana peel polysaccharides. Hence, the present research study was conducted to identify the best pretreatmentconditions particularly for hydrothermal pretreatment with respect to temperature, pH and substrate ratio in order to produce high POS.Prior to the pretreatment, the banana peel hydrolysate was characterized to measure the C, N,,H and S elements by a CHNS elemental analyzer as well as the cell wall’s morphologyusing FESEM. Next, the hydrothermal pretreatment method started by varying the temperature with three different valuesof105°C, 120°C, and 135°C by using an autoclave followed by pH varied at (3, 4, and 5), and lastly different substrate ratio (1:5, 1:10, and 1:15 of solid: liquid ratio, w/v). After that, DNS method was chosen to determine the amount of reducing sugar i.e. POS in each sample. The study's findings suggest that the highest amount of reducing sugar POS was achieved by using UV/Vis spectroscopy at an absorbance of 540 nm were at a temperature of 135°C, pH of 5, and a substrate ratio of 1:15 (w/v). Furthermore, the CHNS elemental analyzer shows the percentage of C, H, N and S element from the banana peel whereby the carbon has the highest percentage also, the morphology of raw and pretreated banana peel has been compared and revealed.In conclusion, the study has successfully recovered high POS from banana peel hydrolysate via hydrothermal pretreatment whereby the highest POS measured was 44.60 mg/mL and the increment of yield calculated was about 418%.